Continuous preparation of carbon-nanotube-supported platinum catalysts in a flow reactor directly heated by electric current - Schlange, Alicja; dos Santos, Antonio Rodolfo; Kunz, Ulrich; Turek, Thomas (Beilstein Journal of Organic Chemistry, 2011)
In this contribution we present for the first time a continuous process for the production of highly active Pt catalysts supported by carbon nanotubes by use of an electrically heated tubular reactor. The synthesized catalysts show a high degree of dispersion and narrow distributions of cluster sizes. In comparison to catalysts synthesized by the conventional oil-bath method a significantly higher electrocatalytic activity was reached, which can be attributed to the higher metal loading and smaller and more uniformly distributed Pt particles on the carbon support. Our approach introduces a simple, time-saving and cost-efficient method for fuel cell catalyst preparation in a flow reactor which could be used at a large scale.
Keywords: carbon nanotubes; continuous catalyst synthesis; direct electrical heating; flow reactors; fuel cell platinum catalyst